IMPLIKASI PERUMUSAN DELIK KORUPSI DI DALAM KEBIJAKAN PEMBAHARUAN KITAB UNDANG-UNDANG HUKUM PIDANA - Syaputra Syaputra (Fiat Justisia: Jurnal Ilmu Hukum, 2015)
The Criminal Code as a legacy of Dutch colonialism could no longer follow the dynamism of community life. It is too rigid has obliterated the sense of justice which is the goal of the creation of the law itself. This is because the articles of the Criminal Code deemed unsuitable to the development of crime and offenses increasingly complex. In the draft Code of Criminal Law, as one of the reform effort is the formulation of offenses of corruption set out in Chapter XXXII starting from Article 688 to Article 702. With the formulation of the offense of corruption and offenses positions formulated in the draft Criminal Code will disregard the Law Combating Corruption although this law of particular importance because of the substance of the articles draft Criminal Code wants to make corruption has become common crimes and do not pass through handling extraordinary. Law on Corruption Eradication cannot apply even if there is the principle of lex specialis derogat lex generalis, because of the retroactive principle that applies in the draft Criminal Code so that the decision to force the law can still be applied retroactively when the rule of law that new does not regulate the offense of criminal, so punishment can be eliminated.Keywords: Offense Corruption , Corruption , Reform of draft Criminal Code